PELATIHAN DAN PENDAMPINGAN PEMBUKUAN PADA USAHA MIKRO KECIL MENENGAH (UMKM) - Gustiningsih, Diah Ayu; Alimuddin, Muh. Ilham; Praditha, Riza; Aisyah, Nur; Muliana, Sitti; Kamal, Arman; Andardinata, Ady (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in maintaining the Indonesian economy. MSMEs that are empowered, are able to open jobs and participate in increasing the capacity of community welfare. To be empowered and develop, MSMEs need good financial literacy to support their operations. The results of the Focus Group Discussion found that the lack of ability to carry out basic bookkeeping is a common problem, as well as the underlying basic assumption that this requires excess time and cost causing MSMEs to be reluctant to carry out bookkeeping routines for their business activities. The purpose of this training and assistance in bookkeeping is to increase the awareness of MSMEs in conducting bookkeeping and maintaining the stability of their business by making it easier to record transactions in their business. Direct practice and mentoring methods were chosen as methods in this community service.